Diversity in chemical structures and biological properties of plant alkaloids - Bhambhani, Sweta; Kondhare, Kirtikumar R.; Giri, Ashok P. (Molecules, 2021)
Phytochemicals belonging to the group of alkaloids are signature specialized metabolites endowed with countless biological activities. Plants are armored with these naturally produced nitrogenous compounds to combat numerous challenging environmental stress conditions. Traditional and modern healthcare systems have harnessed the potential of these organic compounds for the treatment of many ailments. Various chemical entities (functional groups) attached to the central moiety are responsible for their diverse range of biological properties. The development of the characterization of these plant metabolites and the enzymes involved in their biosynthesis is of an utmost priority to deliver enhanced advantages in terms of biological properties and productivity. Further, the incorporation of whole/partial metabolic pathways in the heterologous system and/or the overexpression of biosynthetic steps in homologous systems have both become alternative and lucrative methods over chemical synthesis in recent times. Moreover, in-depth research on alkaloid biosynthetic pathways has revealed numerous chemical modifications that occur during alkaloidal conversions. These chemical reactions involve glycosylation, acylation, reduction, oxidation, and methylation steps, and they are usually responsible for conferring the biological activities possessed by alkaloids. In this review, we aim to discuss the alkaloidal group of plant specialized metabolites and their brief classification covering major categories. We also emphasize the diversity in the basic structures of plant alkaloids arising through enzymatically catalyzed structural modifications in certain plant species, as well as their emerging diverse biological activities. The role of alkaloids in plant defense and their mechanisms of action are also briefly discussed. Moreover, the commercial utilization of plant alkaloids in the marketplace displaying various applications has been enumerated.
Keywords: alkaloid; Biological activity; classification; defense; Enzyme; modification

Dietary influence on modulation of Helicoverpa armigera oral secretion composition leading to differential regulation of tomato plant defense - Gopal S. Kallure; Balkrishna A. Shinde; Vitthal T. Barvkar; Archana Kumari; Ashok P. Giri (Plant Science, 2022)
Little is known about how different plant-based diets influence the insect herbivores’ oral secretion (OS) composition and eventually the plant defense responses. We analyzed the OS composition of the generalist Lepidopteran insect, Helicoverpa armigera feeding on the host plant tomato (OSH), non-host plant capsicum (OSNH), and artificial diet (OSAD) using Liquid Chromatography-Quadrupole Time of Flight Mass Spectrometry. Higher numbers and levels of alkaloids and terpenoids were observed in OSH and OSNH, respectively while OSAD was rich in phospholipids. Interestingly, treatment of H. armigera OSAD, OSH and OSNH on wounded tomato leaves showed differential expression of (i) genes involved in JA and SA biosynthesis and their responsive genes, and (ii) biosynthetic pathway genes of chlorogenic acid (CGA) and trehalose, which exhibited increased accumulation along with several other plant defensive metabolites. Specifically, high levels of CGA were detected after OSH and OSNH treatments in tomato leaves. There was higher expression of the genes involved in phenylpropanoid biosynthesis, which may lead to the increased accumulation of CGA and related metabolites. In the insect bioassay, CGA significantly inhibited H. armigera larval growth. Our results underline the differential accumulation of plant and insect OS metabolites and identified potential plant metabolite(s) affecting insect growth and development.
Keywords: Chlorogenic acid; defense; Metabolites; Non-host; Oral secretion; trehalose

Dietary influence on modulation of Helicoverpa armigera oral secretion composition leading to differential regulation of tomato plant defense. - Kallure, Gopal S.; Shinde, Balkrishna A.; Barvkar, Vitthal T.; Kumari, Archana; Giri, Ashok P. (Plant Science, 2022)
Little is known about how different plant-based diets influence the insect herbivores' oral secretion (OS) composition and eventually the plant defense responses. We analyzed the OS composition of the generalist Lepidopteran insect, Helicoverpa armigera feeding on the host plant tomato (OSH), non-host plant capsicum (OSNH), and artificial diet (OSAD) using Liquid Chromatography-Quadrupole Time of Flight Mass Spectrometry. Higher numbers and levels of alkaloids and terpenoids were observed in OSH and OSNH, respectively while OSAD was rich in phospholipids. Interestingly, treatment of H. armigera OSAD, OSH and OSNH on wounded tomato leaves showed differential expression of (i) genes involved in JA and SA biosynthesis and their responsive genes, and (ii) biosynthetic pathway genes of chlorogenic acid (CGA) and trehalose, which exhibited increased accumulation along with several other plant defensive metabolites. Specifically, high levels of CGA were detected after OSH and OSNH treatments in tomato leaves. There was higher expression of the genes involved in phenyl-propanoid biosynthesis, which may lead to the increased accumulation of CGA and related metabolites. In the insect bioassay, CGA significantly inhibited H. armigera larval growth. Our results underline the differential accumulation of plant and insect OS metabolites and identified potential plant metabolite(s) affecting insect growth and development.
Keywords: Chlorogenic acid; defense; Metabolites; Non-host; Oral secretion; trehalose

MYB proteins: Versatile regulators of plant development, stress responses, and secondary metabolite biosynthetic pathways - Bhatt, Preshita A.; Gurav, Tanuja P.; Kondhare, Kirtikumar R.; Giri, Ashok P. (International Journal of Biological Macromolecules, 2025)
MYB proteins are ubiquitous in nature, regulating key aspects of plant growth and development. Although MYB proteins are known for regulating genes involved in secondary metabolite biosynthesis, particularly phenylpropanoids, their roles in terpenoid, glucosinolate, and alkaloid biosynthesis remain less understood. This review explores the structural and functional differences between activator and repressor MYB proteins along with their roles in plant growth, development, stress responses, and secondary metabolite production. MYB proteins serve as central hubs in protein-protein interaction networks that regulate expression of numerous genes involved in the adaptation of plants to varying environmental conditions. Thus, we also highlight key interacting partners of MYB proteins and their roles in these adaptation mechanisms. We further discuss the mechanisms regulating MYB proteins, including autoregulation, epigenetics, and post-transcriptional and post-translational modifications. Overall, we propose MYB proteins as versatile regulators for improving plant traits, stress responses, and secondary metabolite production.
Keywords: Activator; defense; Development; MYB protein; Repressor; Secondary metabolites

Phenylpropanoid-specific glycosyltransferases from mango and their potential role in defense - Vare, Tejas; Joshi, Rakesh; Liao, Jieren; Hoffmann, Thomas; Schwab, Wilfried; Giri, Ashok (Plant Physiology and Biochemistry, 2026)
Alphonso mango (Mangifera indica cv. Alphonso) is a cornerstone of India's fruit industry due to its distinct aroma and shelf-life characteristics. The uridine diphosphate-dependent glycosyltransferases (UGTs) play a crucial role in stabilising aroma and defense-related specialised metabolites in fruits. The present study explores the potential role of UGTs during mango ripening and Colletotrichum gloeosporioides infection. Gene expression analysis indicated that UGTs showed dynamic expression in skin and pulp during ripening. Phylogenetic analysis revealed substrate-driven divergence of UGTs, with MiUGT92A14 and MiUGT95B15 forming distinct clades associated with flavonoid glycosylation. Recombinant UGTs showed a higher preference for UDP-glucose, which is corroborated by the high accumulation of UDP-glucose during ripening. Furthermore, it was observed that MiUGT92A14 prefers phenolic acids as substrates, while MiGT95B15 shows flavonoid specificity. Spore germination assays demonstrated that both aglycones and their glycosylated derivatives suppressed early fungal morphogenesis, supporting a role for UGT-mediated glycosylation in maintaining defense-related metabolites in a bioactive yet non-toxic form during fruit ripening. Additionally, Colletotrichum gloeosporioides inhibition assays demonstrated that glycosylated products of selected UGTs exhibited equal or enhanced antifungal activity compared with their aglycone forms, indicating that glycosylation promotes the safe accumulation of antifungal compounds by reducing aglycone toxicity to the plant. These findings suggest that glycosylation of specific metabolites is a key for ripening process and to potentiate defence against fungal pathogen.
Keywords: Anthracnose; defense; Flavonoid; Glycoconjugates; Uridine diphosphate-dependent glycosyl-transferase